The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1007/s11999-014-3591-0
|View full text |Cite
|
Sign up to set email alerts
|

Heterotopic Ossification of the Elbow Treated With Surgical Resection: Risk Factors, Bony Ankylosis, and Complications

Abstract: Background Heterotopic ossification is the most common extrinsic cause of elbow contracture and may lead to clinically important stiffness, and rarely, complete bony ankylosis. Surgery sometimes is performed to treat this problem, and published reports differ regarding the factors that are associated with success or failure after this operation and whether the procedure is effective for patients with elbow ankylosis. Questions/purposes We wished (1) to identify potential patient characteristics and modifiable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(43 citation statements)
references
References 19 publications
0
38
0
2
Order By: Relevance
“…Previously, Salazar D et al evaluated the same patients included in this study for modifiable risk factors associated with improved ROM after surgery, compared the ROM gains between patients with complete ankylosis and partially restricted ROM, and to characterize the complications treated with this surgical management and rehabilitation program [20]. In the previously published report, the authors found only hypertension; obesity and transposition of the ulnar artery were associated with worse outcomes.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Previously, Salazar D et al evaluated the same patients included in this study for modifiable risk factors associated with improved ROM after surgery, compared the ROM gains between patients with complete ankylosis and partially restricted ROM, and to characterize the complications treated with this surgical management and rehabilitation program [20]. In the previously published report, the authors found only hypertension; obesity and transposition of the ulnar artery were associated with worse outcomes.…”
Section: Discussionmentioning
confidence: 97%
“…These patients included in this study have previously been reviewed but not specifically evaluated for the effects of workers compensation claims in a previously published study [20].…”
Section: Page -02mentioning
confidence: 99%
“…His radial nerve palsy recovered but deep infection required repeated surgical procedures. Salazar et al in a retrospective study of 46 elbows which underwent surgical excision of HO reported adverse outcomes in preoperative to the final arc of motion of the elbow joint in patients with hypertension, obesity, and absence of peroperative anterior transposition of the ulnar nerve 9 . They reported an average of 17 %( 8 of 46 cases) postoperative complications associated with HO excision.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have recommended the choice of surgical approach, and the technique for excision of HO 8,9,16,17 . We routinely transposed ulnar nerve in all of our cases.…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, although surgical treatment of HO is technically demanding and accompanied by high complication rates, there are studies which report good results after surgical treatment of elbow stiffness due to HO [4,[22][23][24]. Accordingly, there are studies that demonstrate better results for the HO group in comparison with the capsular contracture group after surgical treatment 7.…”
Section: Discussionmentioning
confidence: 99%